Occurrence and Removal of Engineered Nanoparticles in Drinking Water Treatment and Wastewater Treatment Processes. Issue 3 (3rd July 2017) - Park, Chang Min; Chu, Kyoung Hoon; Her, Namguk; Jang, Min; Baalousha, Mohammed; Heo, Jiyong; Yoon, Yeomin
Abstract : The increase in use of engineered nanoparticles (ENPs) ends up in waste streams, and consequently to the environment and drinking water resources. Thus, there is a continuing need to detect and quantify ENPs in water. Understanding ENPs occurrence and behavior in aquatic environments is also required to assess the associated environmental impact. Indeed, insufficient water and wastewater treatment for ENPs may cause a serious threat to the environment and human health. The contaminant removal in conventional drinking water treatment depends largely on the influent quality and operation parameters. A question remains as to whether these processes are also efficient for removal of ENPs and thus for the protection of the public from exposure to ENPs. ENPs can be biodegraded or sorbed by bacterial communities to differing extents, affected greatly by their surface properties, speciation, and transformations in wastewater treatment. Although the available literature is insufficient, the present review attempts to summarize several topics concerning the detection and removal of ENPs that might undergo dissolution, agglomeration, bioaccumulation and transformation in drinking water and wastewater treatment processes.